Tanggung Jawab Notaris dalam Proses Pembuatan Akta Otentik dengan Menggunakan Format Bahasa Asing (Studi Kasus Putusan Pengadilan Negeri Jakarta Barat Nomor 451/Pdt.G/2012/PN.Jkt.Bar) - Alief, Nauval; Marjon, Dahlil; Ferdi, Ferdi (UNES Law Review, 2023)
The purpose of this study is to determine the judge's considerations in case decision number 451/Pdt.G/2012/PN.Jkt.Bar is related to the responsibilities of a notary in the process of making an authentic deed using a foreign language format and what are the responsibilities of a notary in the process of making an authentic deed by using a foreign language format associated with case number 451/Pdt.G/2012/PN.Jkt.Bar. The research method used is Normative Juridical, namely an approach that is based on the main legal material by examining the theories, concepts, legal principles, and laws and regulations related to this research. The results of the research study show that regarding the responsibilities of a notary in the process of making an authentic deed using a foreign language format are linked to case number 451/Pdt.G/2012/PN.Jkt.Bar, stating that a deed that is not made by statutory regulations can result in a deed only having the power of proof under the hand or even null and void.